Efek Moderasi Pendidikan pada Pengaruh Pendapatan dan Konsumsi terhadap Pertumbuhan Ekonomi di Wilayah Gerbangkertosusila - Muhlisin, Muhlisin; Sakti, Norida Canda (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2024)
This study examines the effect of income on the economy and the effect of consumption on economic growth both directly and after being moderated by education in the Gerbangkertosusila region from 2010 to 2019. The purpose of this research is to identify the determinants of economic growth using direct and indirect effects. The tests were carried out through two models and data analysis techniques using moderation regression analysis with the help of SPSS applications v 3.5. The results showed that the two models of direct influence of income and consumption had a positive and significant effect on economic growth, while those that were moderated by education had a positive interaction value or strengthened significantly to the income variable and the consumption variable with economic growth. As a moderating variable in this study, of course, education has a very big role in increasing the growth and development of the region. Further, the result of this study can be a public study of the government so that it always pays attention to and improves the quality of regional education.